The Art of Life in South Africa - Magaziner, Daniel R. (Book collections on Project MUSE., 2016)
From 1952 to 1981, South Africa's apartheid government ran an art school for the training of African art teachers at Indaleni, in what is today KwaZulu-Natal. The Art of Life in South Africa is the story of the students, teachers, art, and politics that circulated through a small school, housed in a remote former mission station. It is the story of a community that made its way through the travails of white supremacist South Africa and demonstrates how the art they made together became the art of their lives. The Art of Life in South Africa proposes a radical reframing of apartheid era South African history. Against the dominant narrative of apartheid oppression and black resistance, as well as recent scholarship that explores violence, criminality and the hopeless entanglements of the apartheid state, this book focuses instead on a small group's efforts to fashion more fulfilling lives for themselves and their community through the ironic medium of the apartheid-era school. There is no book like this in South African historiography. Lushly illustrated and poetically written, it gives us fully formed lives that offer remarkable insights into the now cliched experience of black life under segregation and apartheid.